The Comparative Study of Papain Enzyme from Papaya Fruits California variant and Indonesian Local variant - Diah Ratna Ningrum; Wawan Kosasih; Sri Priatni (Research Center for Chemistry - LIPI, 2017)
Papain (E.C.3.4.22.2) is a proteolytic enzyme which has important role due toits diverse uses in textile, pharmaceutics, cosmetics and food industries.Papain enzyme can be found in almost all parts of the papaya plant and mostof the stem and fruit. The objective of this study is to compare the Californiavar. and Indonesian local var. of papaya fruits, in papain production and alsoto characterize the enzyme properties. Results showed that the highest yield ofcrude papain was obtained from local papaya latex (24.87%) whichprecipitated by ethanol with ratio of 1:2. The highest of activity enzyme,soluble protein and specific enzyme activity obtained from the local papayawere 3154 ± 11.31unit/mL, solubility protein of 0.94± 0.08 mg/mL andspesific enzyme activity of 3355.32 unit/mg protein, respectively. The activityof enzyme fraction F7 obtained from purification by DEAE sepharose columnwas 202.33 U/mL dan the molecular weight of this fraction was between 17-28 kDa.© 2